Modulation of CCR5 expression and R5 HIV-1 infection in primary macrophages exposed to sera from HESN, LTNP, and chronically HIV-1 infected people with or without natural antibodies to CCR5 - Iole Farina; Mauro Andreotti; Claudia Pastori; Roberta Bona; Clementina Maria Galluzzo; Roberta Amici; Cristina Purificato; Caterina Uberti-Foppa; Agostino Riva; Maria Cristina Gauzzi; Lucia Lopalco; Laura Fantuzzi (Virus Research)
CCR5 is the main co-receptor for HIV-1 cell entry and it plays key roles in HIV-1 mucosal transmission. Natural anti-CCR5 antibodies were found in HIV-1-exposed seronegative and long-term non-progressor subjects, suggesting a role in controlling viral replication in vivo. We assessed the effect of sera containing or not natural anti-CCR5 antibodies, on membrane CCR5 level and HIV-1 infection in primary macrophages. Sera modulated CCR5 expression with a trend dependent on the donor/serum tested but independent on the presence or absence of anti-CCR5 antibodies. All sera strongly reduced HIV-1 DNA in all donor's macrophages and no correlation was observed between CCR5 and viral DNA levels. These results suggest that CCR5 expression level is not a major determinant of macrophage infection and that the observed modulation of CCR5 and HIV-1 DNA might depend on factors other than CCR5-reactive antibodies present in sera and/or intrinsic to the donors on which sera were tested.